Anomaly detection In IoT using machine learning algorithms - Arko, Aritro Roy; Khan, Saadat Hasan; Preety, A a Anjum; Biswas, Mehrab Hossain (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.